Highly Stable Zero-Dimensional Lead-Free Metal Halides for X-ray Imaging - Han, Joo Hyeong; Samanta, Tuhin; Park, Yong Min; Kim, Ha Jun; Manikanta Viswanath, Noolu Srinivasa; Kim, Hyeon Woo; Cha, Bo Kyung; Cho, Sung Beom; Im, Won Bin (ACS Energy Letters, 2023)
Scintillators are widely used for radiation detection in various fields, such as medical imaging, nondestructive testing, and crystallography. X-ray-generating systems typically emit large amounts of heat and require a high thermal stability of scintillators, particularly for nondestructive testing or radiation detection performed under harsh conditions. Therefore, highly stable scintillators must be developed for application in extreme environments. Herein, we developed new zero-dimensional lead-free monoclinic phases of Cs3TbCl6 and Rb3TbCl6 metal halides that are thermally and chemically stable. Cs3TbCl6 and Rb3TbCl6 polycrystals exhibit high light yields of 56800 and 88800 photons/MeV, respectively. Cs3TbCl6 and Rb3TbCl6 polycrystals also show low detection limits of 149.65 and 115.38 nGyairs-1 due to their structural-optical properties, respectively. Furthermore, the fabricated thick films of Cs3TbCl6 and Rb3TbCl6 are applied to our homemade X-ray imaging system, and preferable spatial resolutions are obtained as compared with a commercial Gd2O2S:Tb3+ film.
Keywords: Condition; Extreme environment; Free metals; Generating system; High thermal stability; Highly stables; Large amounts; Lead-Free; Radiation detection; Zero-dimensional